Analisis Kemampuan Literasi Sains Siswa Sma Pada Pembelajaran Fisika Di Masa Pandemi Covid-19 Terhadap Materi Kinematika Gerak Lurus (IPF: Inovasi Pendidikan Fisika, 2022)
Abstract During the Covid-19 pandemic, less than optimal learning had an impact on students' physical science literacy skills, especially based on an assessment conducted by PISA that Indonesian students' scientific literacy abilities were classified as low. Therefore, efforts are needed to improve students' scientific literacy skills.The purpose of this study was to analyze the scientific literacy skills of students of class X MIPA 1 and X MIPA 2 at SMA Negeri 1 Pangkalan Banteng on the material of straight motion kinematics for learning physics during the covid-19 pandemic. This research is included in quantitative descriptive research. The sampling technique of this research is cluster random sampling. The sample of this research is 62 students from two classes, namely X MIPA 1 and X MIPA 2 SMA Negeri 1 Pangkalan Banteng. Data collection techniques are by means of interviews and online tests by working on essay questions that have been validated by the validator. The level of scientific literacy ability that is measured is the domain of competence. From the results of the study, it was found that the level of physical science literacy skills of students, especially in straight motion kinematics material was classified as "Low" with a percentage of 56%. So, the need for activities such as scientific literacy-based practicums can attract students' curiosity and strengthen students' understanding of concrete science through an experiment, even though learning is done online. Keywords: Science Literacy Ability, Physics, Covid-19 Pandemic, Straight Motion Kinematics.